Innovative Prosthetic Device New Materials, Technologies and Patients' Quality of Life (QoL) Improvement - Cicciu, Marco; Fiorillo, Luca; De Stefano, Rosa (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
An amputee patient is a patient who has lost not only a part of his body but also the annexed function. The loss of an eye, an arm, or a dental element entails a loss of function reflected in a systemic adaptation by the organism to compensate for it. Moreover, it is reflected in important psychological consequences. The purpose of this Special Issue is to collect as many articles and information about new rehabilitation techniques in the biomedical and bioengineering field as possible. In all organism districts, the focus is on the innovation of a certain material or a specific technique without neglecting the influence on a patient's quality of life.